Analysis of Knowledge, Attitudes, and Practices of Cadres Regarding Growth Monitoring, Provision of Supplementary Food, and Provision of Infant and Child Food in Stunting Locus Areas - Nur Alam Fajar; Rostika Flora; Mohammad Zulkarnain; Ferenadia Apriliani; Devy Yuliantari; Dea Pradisa (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a major problem in Indonesia. Stunting can affect physical, mental, cognitive and intellectual development so that children are unable to learn optimally. Banyuasin Regency is ranked 3rd in toddlers who experience stunting out of 17 districts/cities in South Sumatra. Stunting control is carried out through specific interventions in the form of providing additional food (PMT), monitoring toddler growth, and providing infant and child food (PMBA). The aim of this research is to find out the knowledge, attitudes and behavior of cadres regarding providing additional food, monitoring the growth of toddlers, and feeding babies and children in stunting locus area. This type of research is quantitative with a quantitative research method with a cross-sectional approach. This research was conducted in 3 stunting locus sub-districts in Banyuasin Regency. In August-September 2024. The population in this study were all posyandu cadres in Banyuasin Regency. The sample in this study was 102 posyandu cadres with the Cluster random sampling technique. Data analysis was carried out descriptively. This study shows that there is a need to improve the knowledge, attitudes, and behavior of community health cadres regarding monitoring child growth and providing supplementary feeding. Aspects that need to be strengthened include understanding of signs of growth disorders, age and gender criteria for recipients of supplementary feeding, and involvement in data collection and planning with nutritionists. Further training and closer collaboration are needed to improve program effectiveness.